Genome-Wide Association Mapping for Salt Tolerance of Rice Seedlings Grown in Hydroponic and Soil Systems Using the Bengal and Assam Aus Panel - Chen, Caijin; Norton, Gareth J.; Price, Adam H. (Frontiers in Plant Science, 2020)
Salinity is a major abiotic stress which inhibits rice production in coastal, arid and semi-aid areas in many countries, such as India and Bangladesh. Identification of salt tolerant cultivars, quantitative trait loci (QTLs) and genes is essential for breeding salt tolerant rice. The aus subpopulation of rice is considered to have originated predominantly from Bangladesh and India and have rich genetic diversity with wide variation in abiotic stress resistance The objective of this study was to identify QTLs, and subsequently candidate genes using cultivars from the aus subpopulation and compare the results of two different seedling stage screening methods. Salt tolerance at the rice seedling stage was evaluated on 204 rice accessions from the Bengal and Assam Aus Panel grown in both hydroponics and soil under control and salt stress conditions. Ten salt related traits of stress symptoms, plant growth and the content of sodium and potassium were measured. Three cultivars, BRRI dhan 47, Goria, and T 1 showed more salt tolerance than the tolerant check Pokkali in both systems. Genome-wide association mapping was conducted on salt indices traits with 2 million SNPs using an efficient mixed model (EMMA) controlling population structure and kinship, and a significance threshold of P < 0.0001 was used to determine significant SNPs. A total of 97 and 74 QTLs associated with traits in hydroponic and soil systems were identified, respectively, including 11 QTLs identified in both systems. A total of 65 candidate genes were found including a well-known major gene OsHKT1;5. The most significant QTL was detected at around 40 Mb on chromosome 1 coinciding with two post-translational modifications_SUMOylation genes (OsSUMO1 and OsSUMO2), and the detail information of this QTL was investigated. The salt tolerance rice cultivars and QTLs/genes identified here will provide useful information for future studies on genetics and breeding salt tolerant rice.